Degradation processes in LED modules - Sorokin, V.M.; Kudryk, Ya.Ya.; Shynkarenko, V.V.; Kudryk, R.Ya.; Sai, P.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Electrical-heat-light degradation model of a light-emitting module has been developed in this work. The Monte-Carlo method was used to calculate the reliability time of LED modules with different halfwidth of LED chip series resistance. Separation of LED chips with different series resistance before assembling may increase the time of emission in a stable mode up to 10%.